Donor‐unsupported Phosphanylmethanides Li[CH2PR2] (R = tBu, Ph) – Crystal Structure of Li[CH2PtBu2] Solved by XRPD and DFT‐D Calculations1. Issue 3 (25th January 2016) - Fink, Lothar; Samigullin, Kamil; Bodach, Alexander; Alig, Edith; Wagner, Matthias; Lerner, Hans‐Wolfram
Abstract: The solvent‐free methyllithium derivatives Li[CH2 P R 2 ] ( R = t Bu, Ph) were prepared via the reaction of CH3 P R 2 with Li[ t Bu]. It should be noted that the deprotonation of CH3 P t Bu2 with Li[ t Bu] occurred at 60 °C, whereas Li[CH2 PPh2 ] was already formed from CH3 PPh2 with Li[ t Bu] at ambient temperature. The structure determination of di‐ tert ‐butylphosphanylmethyllithium was performed by high resolution X‐ray powder diffraction analysis at different temperatures. This led to two possible structure solutions with similar quality criteria (space groups Iba 2 and I 2/ a ). Therefore CASTEP DFT‐D calculations were applied to verify the correct crystal structure. The solid‐state structure of di‐ tert ‐butylphosphanylmethyllithium consists of alternating edge‐sharing six‐ and four‐membered rings, which form a polymeric, infinite double‐chain along the crystallographic c axis in the monoclinic space group I 2/ a . Two Li[CH2 P t Bu2 ] units connected via an inversion center form a six‐membered Li2 C2 P2 ring in the chair conformation. The nearly flat four‐membered Li2 C2 ring, is oriented perpendicularly to the twofold axis. Abstract :